Bike fit. Optimise your bike position for high performance and injury avoidance - Burt, P. (Bloomsbury Publishing Plc, 2014)
This practical guide, written by a leading BIKE FIT expert, takes you step-by-step through the BIKE FITprocess - to ensure you maximise your cycling potential. Do you suffer from lower back pain after a longweekend ride? Do your shoes wear out on one side more than the other? Are you experiencingnumbness in your hands, or knee pain? Phil Burt, Head Physiotherapist at British Cycling and Team SkyConsultant Physiotherapist, has worked with hundreds of cyclists to help them solve these and manyother classic cycling niggles. In this book he outlines his methods to help you analyse your position andget the best from your bike., The right BIKE FIT can mean the difference between a good ride and a badone, but a professional fit can cost more than you paid for your bike. The information is all here. Let PhilBurt guide you through your own BIKE FIT, to ensure your bike and body work in harmony., Packed withuseful diagrams, step by step diagnostics and case studies, this is the must-read for any cyclist keen toget a performance advantage.